2006
DOI: 10.1016/j.cub.2006.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Localized Distortions of Event Time

Abstract: A fundamental question about the perception of time is whether the neural mechanisms underlying temporal judgements are universal and centralized in the brain or modality specific and distributed. Time perception has traditionally been thought to be entirely dissociated from spatial vision. Here we show that the apparent duration of a dynamic stimulus can be manipulated in a local region of visual space by adapting to oscillatory motion or flicker. This implicates spatially localized temporal mechanisms in dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
363
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(408 citation statements)
references
References 46 publications
39
363
5
1
Order By: Relevance
“…The results reported here are in strong contrast with the result of studies investigating the effect of adaptation to other temporal and non-temporal stimulus features on perceived duration (Johnston et al, 2006;Ortega et al, 2012;Zhou et al, 2014). In general, these studies report strong spatial selectivity indicating an origin in early visual areas (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results reported here are in strong contrast with the result of studies investigating the effect of adaptation to other temporal and non-temporal stimulus features on perceived duration (Johnston et al, 2006;Ortega et al, 2012;Zhou et al, 2014). In general, these studies report strong spatial selectivity indicating an origin in early visual areas (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, it has been shown that adapting to the temporal frequency content of a stimulus can cause spatially localized shifts in the perceived duration of subsequent events. These spatially selective after-effects following adaptation have been attributed to modulation in neurons in LGN and V1 (Ayhan, Bruno, Nishida, & Johnston, 2009;Johnston et al, 2006;Ortega et al, 2012; but see Burr, Tozzi, & Morrone, 2007;Fornaciai, Arrighi, & Burr, 2016). These findings suggest a strong relation between low-level visual processing and the encoding of temporal information.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies (Burr, Tozzi, & Morrone, 2007;Johnston, Arnold, & Nishida, 2006) have demonstrated that adaptation to high-frequency visual stimuli decreased subjective duration of another visual stimulus at the location where the high-frequency stimulus had been presented. This phenomenon may seem analogous to the present findings.…”
Section: Resultsmentioning
confidence: 99%
“…When a flickering stimulus is presented in a specific region of visual space and leads to local adaptation, there is a reduction of the perceived duration of subsequent stimuli if they are presented in the same specific region, but not if they are presented in other regions of visual space (Johnston, Arnold, & Nishida, 2006). Burr, Tozzi, and Morrone (2007) also reported that the timing of visual events is spatially selective.…”
Section: No Central Clockmentioning
confidence: 99%